New Oral Anticoagulants Open New Horizons for Cancer Patients with Venous Thromboembolism - Wumaier K; Li W; Cui J (Dove Medical Press, 2022)
Kaidireyahan Wumaier,1 Wenqian Li,1 Jiuwei Cui2 1The First Hospital of Jilin University, Jilin University, Changchun, People's Republic of China; 2Department of Cancer Center, the First Hospital of Jilin University, Changchun, People's Republic of ChinaCorrespondence: Jiuwei Cui, Department of Cancer Center, the First Hospital of Jilin University, Changchun, Jilin, 130021, People's Republic of China, Tel/Fax +86-0431-88782178, Email cuijw@jlu.edu.cnAbstract: Venous thromboembolism (VTE) is associated with increased morbidity and mortality, decreased quality of life, and higher economic burden in patients with cancer. Currently, the treatment of VTE in patients with cancer is particularly challenging. For many years, low molecular weight heparin (LMWHs) has been the standard for the treatment of cancer-associated VTE. Recently, the introduction of new oral anticoagulants (NOACs) may offer an oral anticoagulant option for some patients with cancer-associated thrombosis (CAT) as a growing body of literature supports the use of NOACs in the setting of CAT. With the use of NOAC as a new option in the management of CAT, clinicians now face several choices for the individual cancer patient with VTE. We need a more in-depth understanding of the drug properties, efficacy and safety, economic analysis that allows us to choose the most appropriate treatment for each patient. In the review, we will present an overview of CAT management, discuss the available evidence, economic costs for NOACs in the treatment of CAT, and seek to provide the best range of treatments for cancer patients.Keywords: new oral anticoagulants, low molecular weight heparin, venous thromboembolism, cancer-associated thrombosis, anticoagulants